Factors Associated with Appropriate Gestational Weight Gain among Women with Obesity - Cozzi, Gabriella D.; Blanchard, Christina T.; Champion, Macie L.; Todd, Allison; Davis, Margaret; Chandler-Laney, Paula; Casazza, Krista; Casey, Brian M.; Tita, Alan T.; Szychowski, Jeff M.; Subramaniam, Akila (American Journal of Perinatology, 2020)
Objective This study aimed to compare attendance of nutritional counseling, dietary composition, exercise patterns, and socioeconomic factors among obese women with inappropriate gestational weight gain (iGWG) versus appropriate GWG (aGWG).Study Design Medicaid-eligible women receiving prenatal care at a tertiary care center from January 2013 to December 2015 were offered individualized nutritional counseling by a registered dietitian encouraging well-balanced meals and 150 min/wk of exercise. We conducted a prospective case–control study of obese women (body mass index or BMI ≥30) with a singleton gestation with iGWG (<11 or >20 pounds) versus aGWG (11–20 pounds). Dietary intake, activity level, and socioeconomic factors were compared with Chi-square, Fisher's exact, Student's t-test, and Wilcoxon Rank Sum tests as indicated, and odds ratios with 95% confidence intervals were calculated. Multivariate regression analysis for significant variables was performed. A subgroup analysis of women with BMI ≥40 was planned.Results A total of 401 women were analyzed: 78% (n = 313) with iGWG and 22% (n = 88) with aGWG. Demographics were similar between groups. Women with iGWG less frequently reported physician reinforcement of counseling and reported more physical inactivity and unemployment; there were no differences in caloric intake or macronutrient profile between groups. Multivariate regression identified physician reinforcement and employment as independent predictors of aGWG. Among women with BMI ≥40 (n = 133), those with iGWG (78%) were less likely to attend counseling, report physician reinforcement of counseling, and have adequate caloric and protein intake when compared with those with aGWG (22%). Activity level and socioeconomic factors were not different between groups.Conclusion Physician reinforcement of nutritional counseling, greater activity level, and employment are associated with aGWG in women with BMI ≥30, while individualized professional nutritional counseling and dietary modifications were further associated with aGWG in women with BMI ≥40. Thus, greater focus should be placed on enhancing exposure to counseling and altering nutritional and exercise choices to optimize aGWG.Key Points
Keywords: gestational weight gain; nutritional counseling; obesity; social factors